Optimalisasi Minat Baca Siswa melalui Metode Quantum Reading pada Pembelajaran Bahasa Indonesia - Rahma Wahyu; Fitra Jaya Gempawan; Fitria (Kilau Publishing, 2026)
Reading is an important activity in the learning process because through reading, individuals can obtain information, knowledge, and new insights that are useful for their intellectual development. However, based on observations at MI Mambaul Ulum, students' interest in reading is still relatively low. This is evident in the minimal number of students who actively engage in reading, both inside and outside of class. This low interest in reading is influenced by several factors, including the use of ineffective learning methods, inadequate reading facilities, uninteresting teaching materials, and low enthusiasm and motivation among students to participate in reading activities. These conditions have an impact on students' low comprehension of reading materials and suboptimal learning outcomes. Based on these problems, this study aims to increase the reading interest of fourth-grade students at MI Mambaul Ulum through the application of the Quantum Reading method in Indonesian language lessons. The type of research used is Classroom Action Research (CAR) with the Kemmis and Mc. Taggart model, which was carried out in two cycles. The results show that the application of the Quantum Reading method can significantly increase students' reading interest and learning outcomes. In cycle I, the percentage of students' reading interest reached 55.55% with an average learning outcome score of 62.51, which was still in the poor category. Furthermore, in cycle II, there was a significant increase, namely the percentage of students' interest in reading reached 92.59% and the average learning outcome score increased to 82.22, which is in the fairly good category. This shows that the Quantum Reading method is effective in improving the quality of reading learning